Trends and Challenges of Implementing Innovative Bio-Based Construction Materials for Green Infrastructure - Delisma Siregar (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
The construction industry is one of the sectors that has a significant impact on environmental damage due to high energy consumption, exploitation of natural resources, and carbon emissions. In response to these challenges, this study aims to analyze the potential for implementing sustainable construction materials to support the development of green infrastructure. Using qualitative methods through literature studies, documentation, observation, and in-depth interviews, this study evaluates the advantages, challenges, and economic and environmental impacts of various innovative materials, such as foam glass, green wall systems, bamboo composites, eco-cement, and mycelium-based blocks. The results show that these materials are able to reduce carbon emissions, increase building energy efficiency, and offer long-term cost savings. Mycelium-based blocks, in particular, are recorded as the most effective material in reducing construction costs by up to 25% and CO₂ emissions by 250 kg per project. However, the implementation of sustainable materials in Indonesia still faces obstacles such as cost, material availability, and technical regulations. Therefore, synergy is needed between the government, academics, and industry in encouraging research, preparing technical standards, and public awareness campaigns to expand the adoption of environmentally friendly materials in the national construction sector.